(untitled) (Journal of Asian Development Studies, 2026)
Short-and long-run marginal propensities to consume play a critical role in economic development and stimulus policy measures. Insofar as it can be ascertained, there has been no empirical investigation into the magnitude of these Chinese variables. In an effort to fill this gap in the literature, this study specifies and uses available annual data to estimate a distributed lag model to derive the empirical values for these two variables for the Chinese economy. The empirical results reveal that the Chinese short-run MPC is 0.334164 and long-run MPC is 0.8730238 which are in fact much lower than the corresponding figures in emerging and advanced economies, and economies of its neighboring countries in Asia. This in turn suggests that macroeconomic policy is costlier for China, as compared to other countries.